DAMPAK EKONOMI DAN EVALUASI BELANJA DAERAH TERHADAP PEMBANGUNAN DI KABUPATEN BATANGHARI (Studi Kasus : Sektor Pendidikan) - Jasasila Jasasila (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Education Ministry is to provide a broad autonomy in school institutions in the concept of school-based management (SBM). With the MBS school empowerment can be optimally oriented to the four aspects, namely to: improve the quality of education, equity, relevance, and efficiency of education providers. Structurally include: political commitment and policies of the central government (MONE) which is makro.Sedangkan formulation of the problem is: The extent to which the implementation of the program is reason to twelve (12) years in the District of Batang? How the Economic Impact of the development and evaluation of regional expenditure in the education sector development Against Batang District. To analyze the use of secondary data. Furthermore, the data is processed and analyzed descriptively. The first problem formulation will be answered by comparing the components of SPM both elementary school (SD) and high school (SMP) and High School (SMA), which is divided into a number of indicators of achievement of the minimum standards have to be met. The standard is based on the attainment of a minimum percentage, presence or absence of indicators and the increase or decrease in the indicator. Furthermore, achievement of the object studied empirically may be smaller or larger than the Minimum Service Standards (MSS) are determined. As for analyzing economic growth education sector used the model as follows:                                                            (PDRBt – PDRBt-1)Economic Growth  (GDP )  = --------------------------- x 100% PDRBtThe results of the above analysis shows that the contribution of 60% of local government is still happening Gap between the expenses and the cost of education that should be spent both for elementary and junior high school. The dependence of the cost of education is still expecting central contribution that minimum service standards can be achieved. With economic growth (GDP) 21.66% expected a significant economic impact on the development of the education sector in the district of Batanghari. Keyword : economic impact, evaluation, development